Atypical case of neonatal-onset Gaucher disease type 3b: A case report - Takanori Onuki; Kinuko Kojima; Kentaro Sawano; Nao Shibata; Yohei Ogawa; Go Hasegawa; Aya Narita; Hiromi Nyuzuki (Molecular Genetics and Metabolism Reports)
Neonatal-onset Gaucher disease (nGD) is considered perinatal lethal GD, a variant of GD type 2 (GD2), and is associated with collodion skin or hydrops fetalis, hepatosplenomegaly, and involvement of central nervous system (CNS). Pulmonary involvement (PI) and lymphadenopathy (LD) are reported GD complications and have unknown incidence, pathogenesis, and response to treatments. Here, we report the case of a patient diagnosed with nGD with collodion skin who developed only mild neurological symptoms and later died in early childhood due to treatment-resistant PI and LD. A female neonate was born at 38 weeks of gestation (weight: approximately 2012 g, height: 45 cm). She had a collodion skin, hepatosplenomegaly, hemorrhagic plaques, and cholestatic liver disease at birth. She was diagnosed with GD based on decreased glucocerebrosidase enzyme activity, and genetic analysis of GBA1 revealed compound heterozygous mutations of c.1193G > T (p.Arg398Leu) and c.1265_1319del (p.Leu422fs). Intravenous enzyme replacement therapy (ERT) was initiated at the 15 days of age. At the age of 2 years and 2 months, she had a Developmental Quotient of 88 but developed horizontal gaze palsy. At 2 years 8 months of age, she developed mesenteric LD and PI because of which she failed to gain weight and developed tachypnea. She was started on oxygen therapy but died of respiratory failure and malnutrition due to PI and LD at the age of 3 years and 8 months. Pathological autopsy did not reveal the presence of Gaucher cells (GCs) in the liver, spleen, and bone marrow, but all lung macrophages had been transformed to GCs that were draining the alveoli, LD was observed in the mesenteric and mediastinal lymph nodes, and nodules of GCs were formed in bilateral kidneys. In conclusion, nGD with collodion skin is not always classified GD2. Although her phenotype may be classified as GD3b, her clinical course was like severe GD1. In addition, PI and LD are difficult to treat with adequate ERT.